Complementary therapies in education, community extension and research in nursing - Leandra Andréia de Sousa; Natália Rejane Salim; Laís Fumincelli; Iraí Maria de Campos Teixeira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Report the implementation of integrative and complementary practices in a Nursing course at a federal university in the fields of teaching, research and extension. Method: As a reference, the concept of nursing care anchored in the integrality and the avant-garde legacy of Florence Nightingale was used. The report is structured in two topics: the first describes the experience itself, and the second brings a critical reflection about the limits, achievements and challenges. Results: The interaction of integrative practices in nursing and its insertion in teaching, research and extension corroborate holistic care, favor the construction of scientific knowledge in the area and potentially requalify professional training. Final considerations: The insertion of integrative and complementary practices in nursing education can contribute to the consolidation of an integral model of care in SUS towards access and comprehensiveness.